Comportamiento de las pérdidas de energía con la instalación de parques fotovoltaicos - Villar Vázquez, Gretchen; Casas Fernández, Leonardo (My University, 2016)
The objective of this paper is show the behavior of losses of energy in 33 kV net in Villa Clara with the installation of photovoltaic parks. The photovoltaic parks that are examined fall under photovoltaic hybrid systems connected to the net. They obtained the results in the RADIAL program, tool to analyze the losses of energy, with the present-day scenes of generation. The behavior of the network of 33 kV of Villa Clara, specifically in the municipality of Santo Domingo in the key Santa María was analyzed, reaching the comparison of the current situation of the network which is simulated in the RADIAL program once the PFVs were installed. They took two hours of sampling, the hour of maxim demands of the and circuit the 12 hours to be the hour of maximum potency delivered by the photovoltaic park. Peak is important to pay attention to the fact that the losses of lines have an irrelevant decrease, due to the capability of photovoltaic parks, the place of position, and the low time of operation out of the schedule.

El artículo que se presenta tiene como objetivo mostrar el comportamiento de las pérdidas de energía en la red de 33 kV en Villa Clara con la instalación de los parques fotovoltaicos. Los parques fotovoltaicos que fueron analizados se clasifican como sistemas fotovoltaicos híbridos conectados a la red. Los resultados se obtuvieron en el programa RADIAL, herramienta para analizar las pérdidas de energía, con los escenarios de generación actuales. Se analizó el comportamiento de la red de 33 kV de Villa Clara, concretamente en el municipio de Santo Domingo y en el cayo Santa María, hasta llegar a la comparación de la situación actual de dicha red, la que queda simulada en el programa RADIAL una vez instalados los PFV. Se tomaron dos horas de muestreo, la hora de máxima demanda del circuito y las 12 horas por ser la hora de máxima potencia entregada por el parque fotovoltaico. Es importante prestar atención al hecho de que las pérdidas de las líneas tienen una disminución irrelevante, debido a la capacidad de los parques fotovoltaicos, el lugar de ubicación, y el bajo tiempo de operación fuera del horario pico.
BEHAVIOR OF LOSSES OF ENERGY WITH THE INSTALLATION OF PHOTOVOLTAIC PARKS
Keywords: Parques Fotovoltaicos; Pérdidas de Energía; Redes de Distribución